Ultra Low-Power Analog Median Filters - A. Diaz-Sanchez; J. Lemus-Lopez; J. M Rocha Perez; J. Ramirez-Angulo; J. E. Molinar Solis; H. Vazquez-Leal (Radioengineering, 2013)
The design and implementation of three analog median filter topologies, whose transistors operate in the deep weak-inversion region, is described. The first topology is a differential pairs array, in which drain currents are driven into two nodes in a differential fashion, while the second topology is based on a wide range OTA, which is used to maximize the dynamic range. Finally, the third topology uses three range-extended OTAs. The proposed weak-inversion filters were designed and fabricated in ON Semiconductor 0.5 micrometer technology through MOSIS. Experimental results of three-input fabricated prototypes for all three topologies are show, where power consumptions of 90nW in the first case, and 270nW in the other two cases can be noticed. A dual power supply +/-1.5 Volts were used.